CFD modeling of industrial cold box with plate-fin heat exchanger: Focusing on phase change phenomenon. (February 2020) - Zargoushi, A.; Talebi, F.; Hosseini, S.H.
Highlights: An industrial cold box with plate-fin heat exchanger (PFHE) is simulated by CFD. The concept of porous media is applied to simulate the flow in channels. Besides the hydrodynamics and heat transfer, the phase change is studied. LTNE model predicts the best results compared to the other models. Abstract: Cold box with plate-fin heat exchanger (PFHE) is extensively used in liquefied natural gas (LNG) refinery plants. In the present study, a CFD model in ANSYS FLUENT is developed for better understanding the transport phenomena, especially the phase change, in a quite complex plate-fin heat exchanger operated in a gas refining company. The flow channels, ducts and passes of the cold box, are considered in the computational geometry. The porous media technique is introduced in the computational domain due to the excessive increase in the number of computational grids when the fins accounted for in the numerical domain. The flash calculations (FC) technique is coupled with CFD in evaluation of chemical species in the cold box by a user defined function. This study examines the importance of local thermal equilibrium between the porous medium and fluid flow without mass transfer (LTE-non mass), local thermal equilibrium between the porous medium and fluid flow with mass transfer (LTE), and local thermal non equilibrium between the porous medium and fluid flow with mass transfer (LTNE) in simulation of an industrial cold box. Numerical results are compared with the corresponding operational data and the best agreement is obtained by the LTNE approach. The calculated mean relative errors of the LTNE approach for the outlet vapor fraction of streams A, hot stream, B and C, sided cold streams, are 0.15, 0.352, and 0.173%, respectively.